Simultaneous in vivo comparison of water‐filled and air‐filled pressure measurement catheters: Implications for good urodynamic practice. Issue 8 (7th August 2015) - Gammie, A.; Abrams, P.; Bevan, W.; Ellis‐Jones, J.; Gray, J.; Hassine, A.; Williams, J.; Hashim, H.
Abstract : Aims: This study aimed to evaluate whether the pressure readings obtained from air‐filled catheters (AFCs) are the same as the readings from simultaneously inserted water‐filled catheters (WFCs). It also aimed to make any possible recommendations for the use of AFCs to conform to International Continence Society (ICS) Good Urodynamic Practices (GUP). Methods: Female patients undergoing urodynamic studies in a single center had water‐filled and air‐filled catheters simultaneously measuring abdominal and intravesical pressure during filling with saline and during voiding. The pressures recorded by each system at each event during the test were compared using paired t‐test and Bland‐Altman analyses. Results: 62 patients were recruited, of whom 51 had pressures that could be compared during filling, and 23 during voiding. On average, the pressures measured by the two systems were not significantly different during filling and at maximum flow, but the values for a given patient were found to differ by up to 10 cmH2 O. Conclusions: This study shows that AFCs and WFCs cannot be assumed to register equal values of pressure. It has further shown that even when the pdet readings are compared with their value at the start of a test, a divergence of values of up to 10 cmH2 O remains. If AFCs are used, care must be taken to compensate for any pdet variations that occur during patient movement. Before AFCs are adopted, new normal values for resting pressures need to be developed to allow good quality AFC pressure readings to be made. Neurourol. Urodynam. 35:926–933, 2016 . © 2015 Wiley Periodicals, Inc.